1970
DOI: 10.1021/ja00722a009
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric silsesquioxanes, (HSiO3/2)n

Abstract: An improved method has been devised for the preparation of (HSiOs/2)s. The previously unknown higher homologs (HSiOi/,)i0-i6 have also been prepared and characterized. They were isolated from a soluble, silanol-free resin obtained by a rather unusual hydrolysis and condensation procedure whereby water is generated via the sulfonation of an aromatic solvent such as benzene. Evidence for the existence of structural isomerism in the larger cage systems was obtained from nmr studies; i.e., only the octamer and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
0
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(108 citation statements)
references
References 0 publications
7
99
0
2
Order By: Relevance
“…Similar FTIR spectra have been reported for cage-like hydrogen silsesquioxane (HSQ) and other dense (HSiO 1.5 ) n extended network (ladder or random) structures. 17,21,22 Considering the SiÀOÀSi stretching and HÀSiÀO deformation bands ( Figure 1A), previous studies have shown that their intensities and frequencies are related to the structure of the HSiO 1.5 framework, with the high frequency component of these bands (ca. 1160 cm À1 for SiÀOÀSi and ca.…”
Section: ' Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar FTIR spectra have been reported for cage-like hydrogen silsesquioxane (HSQ) and other dense (HSiO 1.5 ) n extended network (ladder or random) structures. 17,21,22 Considering the SiÀOÀSi stretching and HÀSiÀO deformation bands ( Figure 1A), previous studies have shown that their intensities and frequencies are related to the structure of the HSiO 1.5 framework, with the high frequency component of these bands (ca. 1160 cm À1 for SiÀOÀSi and ca.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…23,24 Furthermore, the peak at 465 cm À1 has also been associated with cage-like structures. 21,22 Therefore, it can be concluded that the pore walls in the meso-HSiO 1.5 are composed primarily of mixed ladder network and cage-like HSiO 1.5 structures. The Raman spectra of the as-synthesized and surfactant-extracted samples (Supporting Information Figure S2) show that there is a weak interaction between the surfactant molecules and the HSiO 1.5 walls, causing broadening and a small shift of the HÀSi mode at ca.…”
Section: ' Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSQ is also very sensitive to contamination Figure 18. Schematic representation of the molecular structure of HSQ: (a) cage structure for an eight-corner oligomer; (b) random structure of the resist solution [63]. Reprinted with permission from [63].…”
Section: Brief Introduction To Hsqmentioning
confidence: 99%
“…With these preliminary MS results, we have clearly demonstrated that mass spectrometry with the above-mentioned ionization techniques is an invaluable tool that can be utilized when attempting to solve the challenge set forth by the complexity of hydrogen silsesquioxane materials. [1], has the general chemical composition of (HSiO 3/2 ) 2n where n Ͼ 3. It received much attention after its unique applications as carbonless protective coatings and interlayer dielectrics were successfully demonstrated in the early 1990s for the semiconductor industry [2][3][4].…”
mentioning
confidence: 99%